The Ross 248 Project - Johnson, Les (Charles Les); Roy, Ken; Chiles, Patrick; Osborn, Stephanie; Ziarnick, Brent David, 1978-; Montgomery, Laura; Hoyt, Daniel M.; Hoyt, E. Marshall; Williams, Matthew S., 1974-; Butler, D. J. (David John), 1973-; Hampson, Robert E.; Foster, Monalisa; et al. (Baen Publishing Enterprises, 2024)
"Traveling to the stars will be difficult, but not, perhaps, the most difficult part. What about when we get to another star? What then? Will the planets be immediately habitable? Not likely. Will those who undertook the journey be able to easily turn around and come home if they don't find "Earth 2.0?" Almost certainly not. Therein the lies the challenge: Finding worlds that are potentially habitable and then taking the time, perhaps centuries, to make them compatible with Earth life. They will encounter mysteries and unexpected challenges, but the human spirit will endure. Join this diverse group of science fiction writers and scientists as they take up the challenge of The Ross 248 Project."--